2023
DOI: 10.3390/cimb45030139
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of ALDH1A3-Affinic Compounds on Breast and Prostate Cancer Cell Lines as Single Treatments and in Combination with Doxorubicin

Abstract: Aldehyde dehydrogenase (ALDH) enzymes are involved in the growth and development of several tissues, including cancer cells. It has been reported that targeting the ALDH family, including the ALDH1A subfamily, enhances cancer treatment outcomes. Therefore, we aimed to investigate the cytotoxicity of ALDH1A3-affinic compounds that have been recently discovered by our group, on breast (MCF7 and MDA-MB-231) and prostate (PC-3) cancer cell lines. These compounds were investigated on the selected cell lines as sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The molecules are benzyloxybenzaldehyde derivatives and their binding modes on ALDH1A3 isoform have been computationally confirmed [213]. Additional findings indicated that neither ABMM-15 nor ABMM-16 were significantly cytotoxic to any cell line and co-treatment of each of these compounds with doxorubicin (DOX) on breast cancer lines, MCF7 and MDA-MB-231, and prostate cancer line PC-3 resulted in significantly higher cytotoxic effects than DOX treatment alone [240].…”
Section: Aldh1a3 Specific Inhibitorsmentioning
confidence: 85%
“…The molecules are benzyloxybenzaldehyde derivatives and their binding modes on ALDH1A3 isoform have been computationally confirmed [213]. Additional findings indicated that neither ABMM-15 nor ABMM-16 were significantly cytotoxic to any cell line and co-treatment of each of these compounds with doxorubicin (DOX) on breast cancer lines, MCF7 and MDA-MB-231, and prostate cancer line PC-3 resulted in significantly higher cytotoxic effects than DOX treatment alone [240].…”
Section: Aldh1a3 Specific Inhibitorsmentioning
confidence: 85%